A dictionary of Samaritan Aramaic - Tal, Abraham, 1931- (Handbuch der Orientalistik. Nahe und der Mittlere Osten ;, 2000)
Given the many excellent editions of Samaritan writings (e.g. The Pentateuch) in recent years, the need was felt for a comprehensive dictionary of Samaritan Aramaic. Abraham Tal's Dictionary of Samaritan Aramaic , the first dictionary of its kind, contains the vocabulary of the Aramaic dialect in which the Samaritans composed their texts, from the beginning of their literature in the fourth century C.E. when Aramaic was the community's vernacular, until the end of the use of Aramaic in the eleventh century, when it was replaced by Arabic. Over a period of more than fifteen years the author has exhaustively collected material form the Samaritans' translations of the Pentateuch, their liturgy, literary compositions, chronicles, et cetera, as presented in the growing corpus of scholarly editions. Comparative material from adjacent Palestinian Aramaic dialects is adduced where functional. With ample linguistic and textual notes. Particularly important for the study of Aramaic Jewish and Christian sources composed during the Roman and Byzantine periods in the Land of Israel, and an absolute must for Biblical Scholars . Entries in Samaritan-Aramaic (Hebrew block script); English translations; Hebrew translations; bibliographical abbreviations, et cetera, in English.